Genetic underpinnings of the psoriatic spectrum - Hüffmeier, Ulrike; Klima, Janine; Hayatu, Mohammad Deen (Medizinische Genetik, 2023)
The psoriatic field includes both rare and common subtypes. Common complex forms include psoriasis vulgaris and psoriatic arthritis. In these subtypes, certain HLA alleles remain the most relevant genetic factors, although genome-wide association studies lead to the detection of more than 80 susceptibility loci. They mainly affect innate and adaptive immunity and explain over 28 % of the heritability. Pustular psoriasis comprises a group of rarer subtypes. Using exome sequencing, several disease genes were identified for mainly generalized pustular psoriasis, and an oligogenic inheritance is likely. Treatment studies based on the affected IL-36 pathway indicate a high response rate in this subtype further supporting the pathophysiological relevance of the affected gene products.
CRIS-Team Scopus Importer:2023-05-26
Keywords: HLA; IL36RN; Psoriasis vulgaris; psoriatic arthritis; pustular psoriasis

Symplasmic phloem unloading and radial post-phloem transport via vascular rays in tuberous roots of Manihot esculenta - Mehdi, Rabih; Lamm, Christian; Bodampalli Anjanappa, Ravi; Müdsam, Christina; Saeed, Muhammad; Klima, Janine; Kraner, Max; Ludewig, Frank; Knoblauch, Michael; Gruissem, Wilhelm; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2019)
Cassava (Manihot esculenta) is one of the most important staple food crops worldwide. Its starchy tuberous roots supply over 800 million people with carbohydrates. Yet, surprisingly little is known about the processes involved in filling of those vital storage organs. A better understanding of cassava carbohydrate allocation and starch storage is key to improving storage root yield. Here, we studied cassava morphology and phloem sap flow from source to sink using transgenic pAtSUC2::GFP plants, the phloem tracers esculin and 5(6)-carboxyfluorescein diacetate, as well as several staining techniques. We show that cassava performs apoplasmic phloem loading in source leaves and symplasmic unloading into phloem parenchyma cells of tuberous roots. We demonstrate that vascular rays play an important role in radial transport from the phloem to xylem parenchyma cells in tuberous roots. Furthermore, enzymatic and proteomic measurements of storage root tissues confirmed high abundance and activity of enzymes involved in the sucrose synthase-mediated pathway and indicated that starch is stored most efficiently in the outer xylem layers of tuberous roots. Our findings form the basis for biotechnological approaches aimed at improved phloem loading and enhanced carbohydrate allocation and storage in order to increase tuberous root yield of cassava.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Apoplast; cassava; CFDA; esculin; morphology; phloem; ray; starch; SUC2; symplast